2020
DOI: 10.1002/oby.23034
|View full text |Cite
|
Sign up to set email alerts
|

Body Fatness Influences Associations of Body Composition and Energy Expenditure with Energy Intake in Healthy Women

Abstract: This study aimed to investigate the influence of body fatness on the associations of body composition and energy expenditure (EE) with energy intake (EI). Methods: Data from 93 women (BMI = 25.5 [SD 4.2] kg/m 2) recruited for two studies (Study 1, n = 48, BMI = 25.0-34.9 kg/m 2 ; Study 2, n = 45, BMI = 18.5-24.9 kg/m 2) were examined. Body composition, resting metabolic rate (RMR), and test meal EI were assessed during a laboratory probe day. Physical activity, total daily EE (TDEE), and self-reported freelivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…For example, Grannell et al [10] found a positive association between FFM and ad libitum test meal energy intake in 43 individuals with severe obesity, but the strength of this association was weaker in those with a higher BMI. These findings are supported by Casanova et al [9], who reported that percentage body fat moderated the associations between RMR and total daily energy expenditure with free-living 24-h energy intake. Weaker associations in those with obesity are in line with the notion of leptin resistance [11], and suggests that the relationship between fat mass and energy intake is more variable than with FFM and may be differ depending on the level of adiposity.…”
Section: The Role Of Fat-free Mass and Resting Metabolic In The Contr...supporting
confidence: 73%
See 1 more Smart Citation
“…For example, Grannell et al [10] found a positive association between FFM and ad libitum test meal energy intake in 43 individuals with severe obesity, but the strength of this association was weaker in those with a higher BMI. These findings are supported by Casanova et al [9], who reported that percentage body fat moderated the associations between RMR and total daily energy expenditure with free-living 24-h energy intake. Weaker associations in those with obesity are in line with the notion of leptin resistance [11], and suggests that the relationship between fat mass and energy intake is more variable than with FFM and may be differ depending on the level of adiposity.…”
Section: The Role Of Fat-free Mass and Resting Metabolic In The Contr...supporting
confidence: 73%
“…The findings of McNeil et al [6] that leptin was negatively associated with energy intake are interesting in that previous studies have reported inconsistent findings between fat mass and energy intake, with negative associations reported in lean individuals but no association or weak positive associations seen in those with obesity (see Blundell et al [5]). To examine this issue further, Casanova et al [9] recently investigated the associations between body composition, energy expenditure and energy intake ( ad libitum test meal and free-living 24-h energy intake) in healthy weight ( n = 45) and individuals with overweight or obesity ( n = 48). Fat mass was negatively associated with test meal energy intake in the lean individuals, but no associations were seen in those with overweight or obesity.…”
Section: The Role Of Fat-free Mass and Resting Metabolic In The Contr...mentioning
confidence: 99%
“…As noted by the authors these 'findings suggest that at the extremes of obesity FFM continues to promote hunger and EI' [50, p. 1], but the strength of this association was weaker in individuals with a higher BMI. These findings were supported by Casanova et al [56] who reported that percentage body fat moderated the associations between FFM and free-living 24 h EI in 45 healthy weight and 48 individuals with obesity, with these associations becoming weaker at higher percentage body fat levels. When considered alongside similar findings [54,55,57], these data suggest that excess FM may disrupt the coupling between FFM and EI.…”
Section: Body Composition and Hungersupporting
confidence: 66%
“…Specifically, the FFM-EI relationship is mediated by RMR, which positively relates to meal size and EI [79]. The correlation between RMR and EI occurs independently of FM and BMI [80], although it may be less apparent in people with obesity [81]. It is believed that EI is also driven by habitual TDEE; that is, individuals with increased physical activity and RMR would be expected to have a higher EI to compensate for their higher energy requirements.…”
Section: Relationships Between Dietary Intake and Energy Expenditure In Breast Cancer Survivorsmentioning
confidence: 99%